In Vitro Models, Standards, and Experimental Methods for Tobacco Products. (October 2019) - Aghaloo, T.; Kim, J.J.; Gordon, T.; Behrsing, H.P.
Traditional tobacco products have well-known systemic and local oral effects, including inflammation, vasoconstriction, delayed wound healing, and increased severity of periodontal disease. Specifically in the oral cavity and the lung, cigarette smoking produces cancer, increased infectivity, acute and chronic inflammation, changes in gene expression in epithelial lining cells, and microbiome changes. In recent years, cigarette smoking has greatly decreased in the United States, but the use of new tobacco products has gained tremendous popularity. Without significant knowledge of the oral sequelae of products such as electronic cigarettes, researchers must evaluate current in vitro and in vivo methods to study these agents, as well as develop new tools to adequately study their effects. Some in vitro testing has been performed for electronic cigarettes, including toxicologic models and assays, but these mostly study the effect on the respiratory tract. Recently, direct exposure of the aerosol to in vitro 3-dimensional tissue constructs has been performed, demonstrating changes in cell viability and inflammatory cytokines. For in vivo studies, a universal e-cigarette testing machine or standard vaping regime is needed. A standard research electronic cigarette has recently been developed by the National Institute of Drug Abuse, and other devices delivering aerosols with different nicotine concentrations are becoming available. One of the biggest challenges in this research is keeping up with the new products and the rapidly changing technologies in the industry.